A Review of Subspace Segmentation: Problem, Nonlinear Approximations, and Applications to Motion Segmentation. (13th February 2013) - Aldroubi, Akram
Abstract : The subspace segmentation problem is fundamental in many applications. The goal is to cluster data drawn from an unknown union of subspaces. In this paper we state the problem and describe its connection to other areas of mathematics and engineering. We then review the mathematical and algorithmic methods created to solve this problem and some of its particular cases. We also describe the problem of motion tracking in videos and its connection to the subspace segmentation problem and compare the various techniques for solving it.